2008
DOI: 10.1590/s0066-782x2008001300007
|View full text |Cite
|
Sign up to set email alerts
|

VO2 pico e inclinação VE/VCO2 na era dos betabloqueadores na insuficiência cardíaca: uma experiência brasileira

Abstract: SummaryBackground:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
(45 reference statements)
0
5
0
2
Order By: Relevance
“…Another reference predicts that individuals with VO 2 peak inferior to 10 ml.kg -1 .min -1 indicates an important predictor of cardiac events, and higher than 16 ml.kg -1 .min -1 indicates greater survival chances in these patients. Guimarães et al (2008) evaluated 391 subjects with heart failure, 229 of whom used beta-blockers and 162 who did not use. The Naughton protocol was used to evaluate VO 2 peak.…”
Section: Discussionmentioning
confidence: 99%
“…Another reference predicts that individuals with VO 2 peak inferior to 10 ml.kg -1 .min -1 indicates an important predictor of cardiac events, and higher than 16 ml.kg -1 .min -1 indicates greater survival chances in these patients. Guimarães et al (2008) evaluated 391 subjects with heart failure, 229 of whom used beta-blockers and 162 who did not use. The Naughton protocol was used to evaluate VO 2 peak.…”
Section: Discussionmentioning
confidence: 99%
“…A national database of patients using beta-blockers indicated that peak VO 2 ≤ 10 ml/kg -1 /min -1 indicates an increased risk of cardiovascular events, peak VO 2 between 10 and 16 ml/kg -1 /min -1 represents a moderate risk, and peak VO 2 > 16 ml/kg -1 /min -1 indicate a lower risk. In addition, a VE/VCO 2 slope of > 34 was associated with an increased risk 44 . Patients with NIHF accounted for 68% of the sample.…”
Section: Introductionmentioning
confidence: 94%
“…VO 2 pico inferior a 50% do predito tem alta sensibilidade como fator de risco de morte súbita ou de descompensações recorrentes da IC. Recentes estudos demonstraram superioridade da eficácia ventilatória (VE/VCO 2 slope) em relação ao VO 2 pico no prognóstico de pacientes com IC 8,10 .…”
Section: Teste De Esforço Cardiopulmonarunclassified